Skin-friendly elastic thermal insulation fabric and preparation method thereof

By constructing a composite structure of modified titanium dioxide coated nanosilver in the antibacterial layer and modifying it with cysteine, the long-term effect of nanosilver antibacterial fabrics in humid and hot environments is solved, achieving stable and durable antibacterial effect.

CN119843498AActive Publication Date: 2025-04-18FUJIAN QUANZHOU AIGELE GARMENT CO LTD
View PDF 8 Cites 0 Cited by

Patent Information

Application Number
CN202510314853.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-03-18
Publication Date
2025-04-18
Estimated Expiration
2045-03-18

AI Technical Summary

Technical Problem

The existing nano-silver antibacterial fabrics have insufficient long-term antibacterial performance in humid and hot aerobic environment, and the silver ion release half-life is short, resulting in a decrease in the antibacterial rate.

Method used

By constructing a composite structure of modified titanium dioxide coated nanosilver in the antibacterial layer, and selectively modifying the defect site with cysteine, an antibacterial system with gradient protection is formed to accurately regulate the silver ion release rate.

Benefits of technology

The silver ion release half-life is significantly extended, the stable antibacterial performance under humid and heat conditions is maintained, and the high antibacterial rate can be maintained after multiple washings.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The invention discloses a skin-friendly elastic heat preservation fabric and a preparation method thereof, and relates to the field of fabric manufacturing. According to the fabric, spandex core-spun yarn is used as a raw material; the fabric is coated with an antibacterial layer, and the antibacterial layer is prepared from the following raw materials in percentage by weight: 1 to 3 percent of modified titanium dioxide coated nano-silver and 4 to 6 percent of an adhesive; the modified titanium dioxide coated nano-silver is prepared by soaking the titanium dioxide coated nano-silver in a cysteine solution with the concentration of 1 to 5 mmol, and the soaking time is 3 to 5 hours. The skin-friendly elastic heat preservation fabric has the advantages of being efficient in bacterium resistance, long-acting in slow release, balanced in durability and comfort, close to uncoated fabric in softness and the like.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the field of textile fabrics, and in particular to a skin-friendly elastic thermal insulation fabric and a preparation method thereof. Background Art

[0002] In the field of functional textile development, the synergistic effect of multi-component fiber composite systems has become a key path to achieve comprehensive performance optimization of materials. Taking the preparation of skin-friendly elastic thermal insulation fabrics as an example, the current mainstream technology generally adopts a composite material system of spandex and cotton fibers. Among them, spandex gives the material high resilience, and cotton fibers achieve thermal insulation function through their porous structure and natural hygroscopicity. At the same time, their surface hydroxyl groups can enhance the skin-friendly touch of the fabric. However, this system has significant defects in biosafety. Although the inherent porous hydrophilic properties of cotton fibers are conducive to moisture absorption and heat storage, they are also easy to become a carrier for microbial growth. The lack of effective antibacterial functional groups in its natural fiber structure leads to excessive total colony counts in long-term wearing environments, which may cause skin irritation reactions.

[0003] Existing antibacterial modification technologies mostly use post-finishing processes to load antibacterial agents on the fabric surface. For example, patent CN109267232A discloses an antibacterial silk quilt coated with nanosilver in layers and its preparation method, which achieves broad-spectrum antibacterial by means of the contact sterilization mechanism of silver ions and has good antibacterial durability. However, the nanosilver applied by this method has a high surface energy, and the ionization process is accelerated in a hot and humid environment, resulting in the phenomenon of silver ion burst release, and the silver ion release half-life is short. Although the initial antibacterial rate can reach more than 99%, the antibacterial rate decreases rapidly in the sweat accumulation state after contact with the human body or after washing, which is difficult to meet the market demand for long-term antibacterial. Summary of the invention

[0004] The present application provides a skin-friendly elastic thermal insulation fabric and a preparation method thereof, which can obtain a fabric with high efficiency and long-lasting antibacterial effect, and solve the problem that the long-term antibacterial performance of nano-silver antibacterial fabric is insufficient in a hot and humid aerobic environment.

[0005] In the first aspect, the present application provides a skin-friendly, elastic and thermal insulation fabric, which is made of spandex core-spun yarn, wherein the spandex core-spun yarn has spandex fiber as the core layer and cotton fiber is coated on the outside of the spandex fiber; the fabric is coated with an antibacterial layer, and the raw materials of the antibacterial layer include 1-3wt% modified titanium dioxide-coated nanosilver and 4-6wt% adhesive; the modified titanium dioxide-coated nanosilver is prepared by immersing the titanium dioxide-coated nanosilver in a 1-5mmol cysteine ​​solution for 3-5h.

[0006] In any of the above technical solutions, the proportion of titanium dioxide in the titanium dioxide-coated nanosilver is 15-20wt%.

[0007] In any of the above technical solutions, the particle size of the titanium dioxide-coated nanosilver is 40 to 100 nm.

[0008] The present application achieves precise control of the silver ion release rate by constructing a composite structure of titanium dioxide coated nanosilver in the antibacterial layer. Titanium dioxide is coated on the surface of nanosilver in the form of chemical bonding to form a physical barrier, which can effectively inhibit the direct contact between nanosilver and water molecules and oxygen in the environment, and inhibit the silver ion release phenomenon. However, during the growth of the coating layer, due to deposition, temperature stress and other reasons, titanium dioxide is difficult to achieve complete coverage, resulting in the exposure of some nanosilver sites. These exposed sites become channels for silver ion release in a hot and humid environment. To this end, the present application uses cysteine ​​to selectively modify defective sites, using the thiol group in the cysteine ​​molecule to preferentially form a covalent bond or coordination bond with the silver atom, and its carboxylic acid group self-assembles through intermolecular hydrogen bonds to form a dense monolayer film, which effectively inhibits the oxidation of exposed silver sites. And due to the control of the concentration and immersion time of the cysteine ​​solution, the treatment process has less effect on the hydroxyl density on the surface of titanium dioxide, ensuring the release rate of silver ions and the photocatalytic antibacterial activity of titanium dioxide. This dual protection mechanism significantly prolongs the half-life of silver ion release compared to the unmodified sample.

[0009] It is worth noting that controlling the titanium dioxide content at 15-20wt% is the key to achieving a balance between high antibacterial efficiency and long-term effectiveness. When the proportion of titanium dioxide is lower than 15wt%, the continuity of the coating layer decreases, which is not conducive to controlling the release of silver ions in a hot and humid environment and reducing the long-term effectiveness; when the proportion exceeds 20wt%, titanium dioxide forms an overly thick shell, resulting in a reduction in the effective specific surface area of ​​nanosilver and a decrease in the initial antibacterial rate. In addition, moderately reducing the coating amount can construct a moderate defect structure on the surface of nanosilver, which can not only form a protective layer by directional modification of cysteine, but also provide anchoring sites for the active groups in the adhesive. The binding energy between the particles and the substrate is improved. This chemical bonding can reduce the shedding rate of the modified particles under external forces such as friction and maintain good antibacterial properties.

[0010] In any of the above technical solutions, the preparation method of the titanium dioxide-coated nanosilver is as follows: A reducing agent is added to a silver ion aqueous solution, and a reduction reaction is carried out at 70-90° C. to obtain a silver sol; a titanium dioxide precursor and a dispersant are dripped into the silver sol, and the mixture is dispersed by stirring, and an alkaline solution is dripped to adjust the pH to 10-11 to hydrolyze the titanium dioxide precursor, and then a hydrothermal reaction is carried out, and a titanium dioxide shell layer is obtained after the reaction is completed; the product is centrifuged, washed with water, and then calcined at 500-600° C. to obtain the product.

[0011] Exemplarily, the reducing agent is sodium borohydride or ascorbic acid.

[0012] Exemplarily, the titanium dioxide precursor is tetrabutyl titanate or titanium tetrachloride.

[0013] Exemplarily, the alkaline solution is aqueous ammonia or an aqueous solution of sodium hydroxide.

[0014] In any of the above technical solutions, the dispersant is polyvinyl pyrrolidone.

[0015] In any of the above technical solutions, the adhesive is a polyacrylate emulsion, and the copolymerization monomer of the polyacrylate emulsion contains 10 to 20 wt % of unsaturated dicarboxylic acid.

[0016] In any of the above technical solutions, the unsaturated dicarboxylic acid is selected from at least one of maleic acid, fumaric acid and itaconic acid.

[0017] Exemplarily, the comonomer of the polyacrylate emulsion further includes one or more of styrene, methyl methacrylate, ethyl acrylate, hydroxyethyl acrylate, butyl acrylate, isooctyl methacrylate, and acrylic acid.

[0018] The use of non-cross-linked polyacrylate emulsion helps to maintain the softness and comfort of the fabric, and the antibacterial layer is not easy to crack and peel off. In addition, the main component of polyacrylate emulsion is nanoemulsion particles, which are not easy to coat antibacterial particles, which helps to optimize the release kinetics of nanosilver and the catalytic activity of titanium dioxide, and exert a more efficient antibacterial effect. Using unsaturated dicarboxylic acids as copolymer raw materials, abundant active carboxyl groups can be introduced into the polyacrylate adhesive, and they can be firmly chemically bonded with active groups such as amino groups and hydroxyl groups on the surface of titanium dioxide-coated nanosilver particles or cotton fibers. At the same time, delayed addition of dicarboxylic acid monomers in the synthesis process can promote the enrichment of carboxylic acid groups on the surface of emulsion particles, and produce synergistic effects with the active groups of cysteine-modified particles. This allows the adhesive dosage to be reduced to 4-6wt% to still achieve high particle anchoring, and maintain the moisture permeability and breathability and softness of the fabric, avoiding the obstruction of silver ion diffusion due to excessive coating.

[0019] In any of the above technical solutions, the preparation method of the polyacrylate emulsion is as follows: Adding the comonomers except the unsaturated dicarboxylic acid into the aqueous emulsifier solution, stirring and dispersing to form an aqueous phase; Add the initiator aqueous solution dropwise to the water phase, raise the temperature to carry out copolymerization reaction, and react until the monomer conversion rate is ≥95%; then add unsaturated dicarboxylic acid and continue the reaction. After the reaction is completed, cool down and adjust the pH to 8-9.

[0020] In any of the above technical solutions, the mass ratio of spandex fiber to cotton fiber is 5-20:80-95; the twist of the core-spun yarn is 600-1200 twists / m, the single yarn count of the cotton fiber is 40S-120S, and the spandex fiber specification is 20D-70D.

[0021] In a second aspect, the present application provides a method for preparing a skin-friendly elastic thermal insulation fabric, comprising the following operations: According to the raw material ratio of any of the above-mentioned fabric antibacterial layers, modified titanium dioxide coated nanosilver, adhesive and dispersant are added into water, mixed and dispersed to form an antibacterial finishing liquid; the spandex core-spun yarn fabric is immersed in the antibacterial finishing liquid for double dipping and double rolling, and dried and solidified to obtain the product.

[0022] In any of the above technical solutions, the bath ratio of the double dipping and double rolling is 1:10-20; the single dipping time is controlled at 1-3 min; the rolling rate is set to 70-85%; and the roller line pressure is set to 150-250 N / cm.

[0023] In any of the above technical solutions, the drying is divided into pre-baking and shaping, the pre-baking temperature is 80-100°C, and the heat treatment is 1-2 minutes; the shaping temperature is 130-150°C, and the heat treatment is 2-3 minutes.

[0024] In summary, this application has the following beneficial effects: The present application constructs an antibacterial system with gradient protection by coating nanosilver with titanium dioxide and performing surface modification with cysteine. Among them, the titanium dioxide shell layer inhibits the oxidation of the silver body and optimizes the release kinetics of silver ions. The cysteine ​​molecular membrane blocks the release of nanosilver from exposed sites and enhances the bonding strength between particles, polyacrylate adhesive and fabric. Under hot and humid conditions, the resulting fabric has a stable silver ion release rate and a long release half-life, and maintains a high antibacterial rate on bacteria after multiple washings. At the same time, the low dosage of polyacrylate adhesive and nanoemulsion particles give the antibacterial layer good flexibility, and the antibacterial layer is not easy to crack and fall off, achieving the unity of antibacterial durability, mechanical stability and wearing comfort. DETAILED DESCRIPTION

[0025] Preparation Example 1-1, a modified titanium dioxide coated nanosilver, the preparation steps are as follows: Preparation of silver sol: 16.7 g of silver acetate was dissolved in 200 mL of deionized water, heated to 75 °C and protected by nitrogen. 100 mL of ascorbic acid solution (20 wt%) was slowly added dropwise as a reducing agent under stirring, the dripping rate was controlled at 1 mL / min, and the reaction lasted for 40 minutes to generate silver sol.

[0026] Titanium dioxide coating: The silver sol was cooled to 30°C and 6g of polyvinyl pyrrolidone (molecular weight 40,000) was added. 9.8mL of tetrabutyl titanate was premixed with 60mL of anhydrous ethanol and added to the sol at a rate of 2.5mL / min. Sodium hydroxide solution (2mol / L) was added dropwise under ice bath conditions to adjust the pH to 10.8, and the mixture was transferred to the reactor after magnetic stirring for 3 hours. Hydrothermal reaction was carried out at 170°C for 15 hours, and the precipitate was collected by centrifugation and washed with water until neutral. The precipitate was placed in a vacuum dryer at 60°C for 24 hours, heated to 580°C at 8°C / min under a nitrogen atmosphere, and calcined for 3 hours to obtain titanium dioxide-coated nanosilver particles (TiO2 content 18wt%, particle size 70±10nm).

[0027] Cysteine ​​modification: 10 g of the titanium dioxide-coated nanosilver particles were dispersed in 4 mmol / L cysteine ​​solution (500 mL) and immersed under ultrasound at 50°C for 3 hours. The modified particles were obtained after centrifugal drying.

[0028] Preparation Example 1-2, a modified titanium dioxide coated nanosilver, the preparation steps are as follows: Preparation of silver sol: 12.5 g of silver acetate was dissolved in 150 mL of deionized water, heated to 70 °C and protected by nitrogen. 80 mL of sodium borohydride solution (15 wt%) was slowly added dropwise as a reducing agent under stirring, with a drop rate of 1 mL / min, and reacted for 60 minutes to generate silver sol.

[0029] Titanium dioxide coating: The silver sol was cooled to 30°C and 6 g of polyvinyl pyrrolidone (molecular weight 40,000) was added. 5.2 mL of titanium tetrachloride was dissolved in 50 mL of 0.1 mol / L hydrochloric acid solution and added dropwise to the silver sol, maintaining pH 3.5. After hydrolysis at 75°C for 2 hours, sodium hydroxide solution (2 mol / L) was added dropwise to adjust the pH to 10.5. After magnetic stirring for 3 hours, it was transferred to the reactor. After hydrothermal reaction at 150°C for 18 hours, the precipitate was collected by centrifugation and washed with water until neutral. The precipitate was placed in a vacuum dryer at 60°C for 24 hours, heated to 520°C at 10°C / min under a nitrogen atmosphere, and calcined for 3 hours to obtain titanium dioxide-coated nanosilver particles (TiO2 content 15wt%, particle size 55±8nm).

[0030] Cysteine ​​modification: 10 g of the titanium dioxide-coated nanosilver particles were dispersed in a 3 mmol / L cysteine ​​solution (500 mL) and immersed in an ultrasonic bath at 50°C for 4 hours. The modified particles were obtained after centrifugal drying.

[0031] Preparation Example 1-3, a modified titanium dioxide coated nanosilver, the preparation steps are as follows: Preparation of silver sol: 20 g of silver acetate was dissolved in 250 mL of deionized water, heated to 85 °C and protected by nitrogen. 120 mL of ascorbic acid solution (25 wt%) was slowly added dropwise as a reducing agent under stirring, the dripping rate was controlled at 1 mL / min, and the reaction lasted for 50 minutes to generate silver sol.

[0032] Titanium dioxide coating: The silver sol was cooled to 30°C and 6g of polyvinyl pyrrolidone (molecular weight 50,000) was added. 12.5mL of tetrabutyl titanate was premixed with 60mL of anhydrous ethanol and added to the sol at a rate of 2.5mL / min. Sodium hydroxide solution (2mol / L) was added dropwise under ice bath conditions to adjust the pH to 11.2, and the mixture was transferred to the reactor after magnetic stirring for 3 hours. Hydrothermal reaction was carried out at 190°C for 10 hours, and the precipitate was collected by centrifugation and washed with water until neutral. The precipitate was placed in a vacuum dryer at 60°C for 24 hours, heated to 600°C at 15°C / min under a nitrogen atmosphere, and calcined for 4 hours to obtain titanium dioxide-coated nanosilver particles (TiO2 content 20wt%, particle size 85±10nm).

[0033] Cysteine ​​modification: 10 g of the titanium dioxide-coated nanosilver particles were dispersed in a 1 mmol / L cysteine ​​solution (500 mL) and immersed in an ultrasonic bath at 50°C for 5 hours. The modified particles were obtained after centrifugal drying.

[0034] Preparation Example 1-4, a modified titanium dioxide coated nanosilver, differs from Preparation Example 1-1 in that in the titanium dioxide coating step, the amount of tetrabutyl titanate is reduced to 6.0 mL; the final TiO2 content is 12 wt%, and the particle size is 65 ± 10 nm.

[0035] Preparation Example 1-5, a modified titanium dioxide coated nanosilver, is different from Preparation Example 1-1 in that in the titanium dioxide coating step, the amount of tetrabutyl titanate is reduced to 14.0 mL; the final TiO2 content is 23wt%, and the particle size is 75±10nm.

[0036] Preparation Example 1-6, a modified titanium dioxide-coated nanosilver, is different from Preparation Example 1-1 in that in the cysteine ​​modification step, the cysteine ​​concentration is reduced to 0.5 mmol / L, and the immersion time is 3 hours.

[0037] Preparation Example 1-7, a modified titanium dioxide-coated nanosilver, is different from Preparation Example 1-1 in that, in the cysteine ​​modification step, the cysteine ​​concentration is increased to 8.5 mmol / L, and the immersion time is 3 hours.

[0038] Preparation Example 1-8, a titanium dioxide-coated nanosilver, is different from Preparation Example 1-1 in that titanium dioxide-coated nanosilver particles (TiO2 content 18wt%, particle size 70±10nm) are prepared in the titanium dioxide coating step, the particles and aminopropyltrimethoxysilane are added to ethanol at a mass ratio of 100:2, immersed under ultrasound at 50°C for 2 hours, and centrifuged and dried to obtain modified particles.

[0039] Preparation Example 2-1, a polyacrylate emulsion, is prepared according to the following steps: Dissolve 2.5 g of sodium dodecyl sulfate in 200 g of water to obtain an emulsifier solution for later use; dissolve 1.0 g of ammonium persulfate in 20 g of water, pre-emulsify, and obtain an initiator solution for later use.

[0040] Add 60g methyl methacrylate and 25g butyl acrylate to the emulsifier solution, stir at 300rpm for pre-emulsification for 30 minutes to form a stable aqueous phase. Heat the aqueous phase to 80°C, add the initiator solution at a rate of 0.5mL / min to initiate the polymerization reaction, and keep the reaction warm for 3 hours until the monomer conversion rate is ≥96%.

[0041] 15 g of maleic acid was dissolved in 10 mL of water and added dropwise to the reaction system at a rate of 0.5 mL / min. The reaction was continued for 1 hour. The temperature was lowered to 40°C, the pH was adjusted to 8.5 with ammonia water, and an emulsion with a solid content of 38% was obtained by filtration.

[0042] Preparation Example 2-2, a polyacrylate emulsion, is prepared according to the following steps: Dissolve 3.0g of alkylphenol polyoxyethylene ether (OP-10) and 1.5g of sodium dodecyl sulfate in 200g of water to obtain an emulsifier solution for use; dissolve 1.2g of potassium persulfate in 20g of water, pre-emulsify, and obtain an initiator solution for use.

[0043] 65g styrene and 25g ethyl acrylate were added to the emulsifier solution, and pre-emulsified at 300rpm for 45 minutes to form a stable aqueous phase. The aqueous phase was heated to 78°C, and the initiator solution was added dropwise at a rate of 0.5mL / min to initiate the polymerization reaction. The reaction was kept warm for 3 hours until the monomer conversion rate was ≥96%.

[0044] Dissolve 15g of itaconic acid in 10mL of water, add dropwise to the reaction system at a rate of 0.5mL / min, and continue the reaction for 1.5 hours. Cool to 35°C, adjust the pH to 8.5 with ammonia water, and filter to obtain an emulsion with a solid content of 35% and a glass transition temperature (Tg) of -10°C.

[0045] Preparation Example 2-3, a polyacrylate emulsion, is prepared according to the following steps: 3.0 g of sodium dodecyl sulfate was dissolved in 250 g of water to obtain an emulsifier solution for use; 0.8 g of ammonium persulfate was dissolved in 15 g of water, pre-emulsified, and an initiator solution was obtained for use.

[0046] 50g of methyl methacrylate and 30g of hydroxyethyl acrylate were added to the emulsifier solution, and pre-emulsified at 300rpm for 60 minutes to form a stable aqueous phase. The aqueous phase was heated to 82°C, and the initiator solution was added dropwise at a rate of 1mL / min to initiate the polymerization reaction. The reaction was kept warm for 5 hours until the monomer conversion rate was ≥96%.

[0047] Dissolve 20g of fumaric acid in 20mL of water, add dropwise to the reaction system at a rate of 0.5mL / min, and continue the reaction for 2 hours. Cool to 30°C, adjust the pH to 8.0 with ammonia water, and filter to obtain an emulsion with a solid content of 40%.

[0048] Preparation Example 2-4 is a polyacrylate emulsion, which differs from Preparation Example 2-1 in that maleic acid is replaced by an equal amount of acrylic acid.

[0049] Preparation Example 2-5, a polyacrylate emulsion, is different from Preparation Example 2-1 in that maleic acid, methyl methacrylate and butyl acrylate are added to the emulsifier solution to prepare the aqueous phase, and the steps are as follows: Dissolve 2.5 g of sodium dodecyl sulfate in 200 g of water to obtain an emulsifier solution for later use; dissolve 1.0 g of ammonium persulfate in 20 g of water, pre-emulsify, and obtain an initiator solution for later use.

[0050] Add 60g methyl methacrylate, 25g butyl acrylate and 15g maleic acid to the emulsifier solution, stir at 300rpm for pre-emulsification for 30 minutes to form a stable aqueous phase. Heat the aqueous phase to 80°C, add the initiator solution at a rate of 0.5mL / min to initiate the polymerization reaction, and keep the temperature for 3 hours until the monomer conversion rate is ≥96%. Cool the product to 40°C, adjust the pH to 8.5 with ammonia water, and filter to obtain an emulsion with a solid content of 38%.

[0051] Embodiment 1, a skin-friendly elastic thermal insulation fabric, is prepared according to the following steps: Prepare 150D spandex core-spun yarn raw material with a twist of 900 twists / m, the core layer of which is 40D spandex and the outer layer is 80S long-staple cotton fiber. The ratio of spandex to cotton fiber is 12:88. Weave it into plain fabric with a warp density of 120 strands / inch, a weft density of 80 strands / inch, and a gram weight of 145g / m 2 .

[0052] Take 20g of the modified titanium dioxide coated nanosilver prepared in Preparation Example 1-1, 50g of the polyacrylate emulsion prepared in Preparation Example 2-1 and 5g of polyvinyl pyrrolidone (K30), add deionized water to make up to 1kg, and disperse by ultrasound at 40kHz for 30min to prepare an antibacterial finishing liquid.

[0053] According to the bath ratio of 1:15, the above plain fabric was subjected to two dipping and two rolling treatments. The single dipping time was 2 minutes, and the interval between two dippings was 10 seconds to drain the liquid. The rolling line pressure was 200N / cm, and the rolling rate was 80%. After the rolling, it was pre-baked in a 90℃ hot air circulation oven for 1.5 minutes, and the moisture residual rate was 12%. Then it was set in a high-temperature stentering setting machine at 140℃ for 2.5 minutes, and the antibacterial layer thickness was 1.2um.

[0054] Embodiment 2, a skin-friendly elastic thermal insulation fabric, is prepared according to the following steps: Prepare 110D spandex core-spun yarn raw material with a twist of 1200 twists / m, the core layer of which is 20D spandex and the outer layer is long-staple cotton fiber with a count of 120S. The ratio of spandex to cotton fiber is 8:92. Weave it into plain fabric with a warp density of 150 strands / inch, a weft density of 100 strands / inch, and a gram weight of 130g / m 2 .

[0055] 12 g of the modified titanium dioxide coated nanosilver prepared in Preparation Example 1-2, 40 g of the polyacrylate emulsion prepared in Preparation Example 2-2 and 3 g of polyvinyl pyrrolidone (K30) were mixed, deionized water was added to make up to 1 kg, and ultrasonic dispersion was performed at 40 kHz for 30 min to prepare an antibacterial finishing liquid.

[0056] According to the bath ratio of 1:20, the above plain fabric was subjected to two dipping and two rolling treatments. The single dipping time was 3 minutes, and the interval between two dippings was 10 seconds to drain the liquid. The rolling line pressure was 150N / cm, and the rolling rate was 70%. After the rolling, it was pre-baked in an 80℃ hot air circulation oven for 2 minutes, and the moisture residual rate was 14%. Then it was put into a high-temperature stentering setting machine at 130℃ for 3 minutes to obtain an antibacterial layer with a thickness of 0.8um.

[0057] Embodiment 3, a skin-friendly elastic thermal insulation fabric, is prepared according to the following steps: Prepare 210D spandex core-spun yarn raw material with a twist of 600 twists / m, the core layer of which is 70D spandex and the outer layer is 40S long-staple cotton fiber. The ratio of spandex to cotton fiber is 18:82. Weave it into plain fabric with a warp density of 100 strands / inch, a weft density of 60 strands / inch, and a gram weight of 160g / m 2 .

[0058] 30 g of the modified titanium dioxide coated nanosilver prepared in Example 1-3, 60 g of the polyacrylate emulsion prepared in Example 2-3 and 8 g of polyvinyl pyrrolidone (K30) were mixed, deionized water was added to make up to 1 kg, and ultrasonic dispersion was performed at 40 kHz for 30 min to prepare an antibacterial finishing liquid.

[0059] According to the bath ratio of 1:10, the above plain fabric was subjected to two dipping and two rolling treatments. The single dipping time was 1 minute, and the interval between two dippings was 10 seconds to drain the liquid. The rolling line pressure was 250N / cm, and the rolling rate was 80%. After the rolling, it was pre-baked in a 100℃ hot air circulation oven for 1 minute, and the moisture residual rate was 12%. Then it was put into a high-temperature stentering setting machine at 150℃ for 2 minutes to obtain an antibacterial layer with a thickness of 1.5um.

[0060] Example 4, a skin-friendly elastic thermal insulation fabric, is different from Example 1 in that, in the antibacterial finishing liquid raw material, the modified titanium dioxide coated nanosilver of Preparation Example 1-1 is replaced by an equal amount of modified titanium dioxide coated nanosilver of Preparation Example 1-4.

[0061] Example 5, a skin-friendly elastic thermal insulation fabric, is different from Example 1 in that, in the antibacterial finishing liquid raw material, the modified titanium dioxide coated nanosilver of Preparation Example 1-1 is replaced by an equal amount of modified titanium dioxide coated nanosilver of Preparation Example 1-5.

[0062] Example 6, a skin-friendly elastic thermal insulation fabric, is different from Example 1 in that, in the raw material of the antibacterial finishing liquid, the polyacrylate emulsion of Preparation Example 2-1 is replaced by an equal amount of the polyacrylate emulsion of Preparation Example 2-4.

[0063] Example 7, a skin-friendly elastic thermal insulation fabric, is different from Example 1 in that, in the antibacterial finishing liquid raw material, the polyacrylate emulsion of Preparation Example 2-1 is replaced by an equal amount of the polyacrylate emulsion of Preparation Example 2-5.

[0064] Example 8 is a skin-friendly elastic thermal insulation fabric. The difference from Example 1 is that in the raw material of the antibacterial finishing liquid, the amount of the polyacrylate emulsion in Preparation Example 2-1 is 80g.

[0065] Comparative Example 1 is a skin-friendly elastic thermal insulation fabric, which is different from Example 1 in that in the antibacterial finishing liquid raw material, the modified titanium dioxide coated nanosilver in Preparation Example 1-1 is replaced by an equal amount of modified titanium dioxide coated nanosilver in Preparation Example 1-6.

[0066] Comparative Example 2 is a skin-friendly elastic thermal insulation fabric, which is different from Example 1 in that in the antibacterial finishing liquid raw material, the modified titanium dioxide coated nanosilver in Preparation Example 1-1 is replaced by an equal amount of modified titanium dioxide coated nanosilver in Preparation Example 1-7.

[0067] Comparative Example 3, a skin-friendly elastic thermal insulation fabric, is different from Example 1 in that, in the raw material of the antibacterial finishing liquid, the modified titanium dioxide coated nanosilver of Preparation Example 1-1 is replaced by an equal amount of the modified titanium dioxide coated nanosilver of Preparation Example 1-8.

[0068] Comparative Example 4 is a skin-friendly elastic thermal insulation fabric, which is different from Example 1 in that the modified titanium dioxide-coated nanosilver in Preparation Example 1-1 is replaced by an equal amount of nanosilver (particle size 60±10 nm) in the antibacterial finishing liquid raw material.

[0069] Performance testing 1. Antibacterial performance test The test was conducted in accordance with AATCC 147-2016, Determination of Antimicrobial Activity of Textiles: Parallel Strike Method.

[0070] Sample preparation: The antibacterial finished fabric samples (Examples 1-8, Comparative Examples 1-4) were cut into 2.5 cm×2.5 cm specimens.

[0071] Test bacteria: Escherichia coli (ATCC 25922), Staphylococcus aureus (ATCC 6538). Bacterial solution concentration 1×10 6 CFU / mL, inoculated on nutrient agar plates.

[0072] Test steps: Place the sample close to the agar surface inoculated with bacterial solution and incubate at 37℃ for 18 hours. Measure the distance from the edge of the sample to the edge of the inhibition zone (unit: mm), and calculate the width of the inhibition zone: inhibition zone width = inhibition zone diameter - sample diameter. If the inhibition zone width is greater than 1mm, it is judged to be effective antibacterial.

[0073] 2. Nanosilver release half-life Sample preparation: The antibacterial layer was mechanically peeled off from the antibacterial finished fabric and ground into powder (particle size < 100 μm).

[0074] Test steps: Weigh 0.5g of coating powder, immerse in 50mL artificial sweat (the preparation of artificial sweat strictly follows ISO105-E04 standard - sweat fastness test method), oscillate at 37℃ constant temperature (speed 120rpm) to simulate the hot and humid environment of the human body. Take 1mL of sample at 0, 6, 12, 24, 48, and 72 hours, remove particulate matter through 0.22um nylon filter membrane, add 1% nitric acid to the sample to stabilize silver ions and prevent adsorption loss. Agilent 7900ICP-MS equipment was used to analyze the silver ion release kinetics, fit the first-order release model, and calculate the silver ion release half-life.

[0075] 3. Antibacterial layer shedding rate test Sample preparation: Cut the antibacterial finished fabric into samples of 20cm×5cm in size, and sew the edges to prevent fiber shedding and interference.

[0076] Initial coating weight determination: Use a precision balance (accuracy 0.1 mg) to weigh the total weight of the sample (including base fabric and coating). Take the uncoated base fabric (same size) from the same batch and weigh it. Calculate the net weight of the coating (W coating ).

[0077] Friction test: According to GB / T 3920-2008 friction test, Martindale abrasion tester is used, and the friction is carried out 3000 times according to the Lissajous figure at a pressure of 12kpa. After friction, the sample is placed in a dust-free environment, and the surface detached material is gently swept onto the weighed filter paper (weighed in advance) with a soft brush. Use a vacuum cleaner (equipped with a 0.45um filter membrane) to collect the residual detached material inside the instrument. Weigh the collected detached material together with the filter paper, and the net weight of the detached material (W detached). Calculate the coating detachment rate: Shedding rate (%) = Wshed / Wcoating×100.

[0078] 4. Fabric softness test Sample preparation: Cut the antibacterial finished fabric into samples of size 20cm×25cm, take 5 pieces (2.5cmx15cm) along the longitude and latitude, and balance them in an environment of 20℃±2℃, 65%±4%RH for 24 hours.

[0079] Test method: Test according to AATCC 202:2014 heart-shaped ring method. Use a heart-shaped ring softness tester (Handle-0-Meter, model 3210). Fold the sample in half into a heart-shaped ring, fix it in a fixture, push the sample through the annular slit at a speed of 100mm / min, and record the maximum resistance value (cN). Repeat 5 times and take the average value as the bending stiffness. Calculate its softness (the higher the value, the softer the fabric): Softness = 1 / bending stiffness × 1000.

[0080] 5. Moisture permeability test Sample preparation: Cut the antibacterial finished fabric into a circular fabric with a diameter of 70 mm (including the antibacterial layer), seal the edges to prevent side leakage, and equilibrate in an environment of 20℃±2℃, 65%±4%RH for 24 hours.

[0081] Test method: Test according to GB / T 12704-2019 moisture absorption method, seal the sample in the mouth of a moisture permeable cup (inner diameter 60mm, depth 25mm), put 50g of anhydrous CaCl2 in the cup. Put it in a constant temperature and humidity chamber, and weigh the total weight of the moisture permeable cup after 24 hours. Calculate moisture permeability: WVT = (W2-W1) / At×24; W1, W2: mass of the moisture permeable cup before and after the test (g); A: Sample moisture permeability area (m 2 ); t: test time (h).

[0082] Table 1. Performance test results

[0083] Analysis of test results: (1) The width of the antibacterial zone of Examples 1-3 is >3.1mm (Escherichia coli) and >2.9mm (Staphylococcus aureus), which is slightly lower than that of Comparative Examples 1, 3, and 4. However, the half-life of silver ion release in Examples 1-3 (54.1-61.3h) is much greater than that in Comparative Examples 1, 3, and 4 (20.2-35.3h). The reason may be that the titanium dioxide coating (15-20wt%) is combined with cysteine ​​modification (3-5mmol), in which the titanium dioxide shell blocks water and oxygen contact, and the cysteine ​​molecules seal the exposed silver sites, effectively inhibiting the burst release of silver ions, achieving sustained release, and forming a stable and durable antibacterial active layer. However, the incomplete coating structure of Comparative Examples 1, 3, and 4 produces burst release, resulting in high initial efficiency but poor long-term effectiveness. Although the half-life of Comparative Example 2 is longer than that of Examples 1-3, its initial antibacterial performance is poor. The reason may be that the cysteine ​​concentration is too high, causing the titanium dioxide surface to assemble and form a film layer, which limits the photocatalytic activity of titanium dioxide and the effective release of nanosilver.

[0084] (2) The coating shedding rate of Examples 1-3 is less than 5%, which is lower than that of Examples 6 and 7 (11.72 and 15.90%). The reason may be that the unsaturated dicarboxylic acid and delayed acid addition (unsaturated dicarboxylic acid) process used in the polyacrylate emulsion makes the carboxylic acid enriched on the surface of the emulsion particles, which cooperates with the cysteine-modified particles and cotton fibers to enhance the bonding force between the particles, the coating and the fabric.

[0085] The shedding rates of Comparative Examples 3 and 4 (10.34% and 15.21%) were higher than those of Examples 1-3. The reason for this is that the silver sites exposed on the antibacterial particles were not assembled to form a dense cysteine ​​monolayer, so that the antibacterial particles were not well anchored with the adhesive and were easily detached due to friction.

[0086] (3) The bending stiffness of Examples 1-3 is 0.89-1.02 cN·cm2, which is close to that of uncoated fabrics (0.85 cN·cm 2 The reason is that the low amount of adhesive added and the bonding form of the latex particles prevent the antibacterial layer from hardening. Example 8 (high adhesive dosage) The bending stiffness is reduced to 0.76 cN·cm 2 , excessive adhesive causes the coating flexibility to decrease.

[0087] 5. Moisture permeability (GB / T12704-2019) 614 Example 1-3: Moisture permeability 4600-5800g / m2.24h, the porous structure of the coating (nanoemulsion particle size 100-200nm) ensures air permeability.

[0088] In summary, the skin-friendly stretch thermal insulation fabric of the present application has the advantages of high-efficiency antibacterial, long-lasting sustained release, balance of durability and comfort, high moisture permeability, and softness close to that of uncoated fabrics. Its comprehensive performance is significantly better than traditional nano-silver antibacterial technology and is suitable for the development of high-end functional textiles.

[0089] This specific embodiment is merely an explanation of the present application and is not a limitation of the present application. After reading this specification, those skilled in the art may make modifications to the present embodiment without any creative contribution as needed, but such modifications are protected by the patent law as long as they are within the scope of the claims of the present application.

Claims

1. A skin-friendly elastic thermal insulation fabric, characterized in that: The spandex core-spun yarn is used as raw material, the spandex core-spun yarn has spandex fiber as the core layer, and cotton fiber is coated on the outside of the spandex fiber; the fabric is coated with an antibacterial layer, and the raw materials of the antibacterial layer include 1-3wt% modified titanium dioxide coated nanosilver and 4-6wt% adhesive; the modified titanium dioxide coated nanosilver is prepared by immersing the titanium dioxide coated nanosilver in a 1-5mmol cysteine ​​solution for 3-5h.

2. The fabric according to claim 1, characterized in that: The titanium dioxide in the titanium dioxide-coated nano-silver accounts for 15-20 wt %.

3. The fabric according to claim 1, characterized in that: The particle size of the titanium dioxide-coated nano-silver is 40-100 nm.

4. The fabric according to claim 1, characterized in that: The preparation method of the titanium dioxide-coated nanosilver is as follows: A reducing agent is added to a silver ion aqueous solution, and a reduction reaction is carried out at 70-90° C. to obtain a silver sol; a titanium dioxide precursor and a dispersant are dripped into the silver sol, and the mixture is dispersed by stirring, and an alkaline solution is dripped to adjust the pH value to 10-11 to hydrolyze the titanium dioxide precursor, and then a hydrothermal reaction is carried out to obtain a titanium dioxide shell layer after the reaction is completed; the product is centrifuged, washed with water, and then calcined at 500-600° C. to obtain the product.

5. The fabric according to claim 4, characterized in that: The dispersant is polyvinyl pyrrolidone.

6. The fabric according to claim 1, characterized in that: The adhesive is polyacrylate emulsion, and the copolymer monomer of the polyacrylate emulsion contains 10-20wt% of unsaturated dicarboxylic acid.

7. The fabric according to claim 6, characterized in that: The unsaturated dicarboxylic acid is at least one selected from maleic acid, fumaric acid and itaconic acid.

8. The fabric according to claim 6, characterized in that: The preparation method of the polyacrylate emulsion is as follows: Adding the comonomers except the unsaturated dicarboxylic acid into the aqueous emulsifier solution, stirring and dispersing to form an aqueous phase; Add the initiator aqueous solution dropwise to the water phase, raise the temperature to carry out copolymerization reaction, and react until the monomer conversion rate is ≥95%; then add unsaturated dicarboxylic acid and continue the reaction. After the reaction is completed, cool down and adjust the pH to 8-9.

9. The fabric according to claim 1, characterized in that: The mass ratio of the spandex fiber to the cotton fiber is 5-20:80-95; the twist of the core-spun yarn is 600-1200 twists / m, the single yarn count of the cotton fiber is 40S-120S, and the specification of the spandex fiber is 20D-70D.

10. A method for preparing a skin-friendly elastic thermal insulation fabric, characterized in that: include: According to the raw material ratio of the antibacterial layer of the fabric as claimed in any one of claims 1 to 9, the modified titanium dioxide coated nanosilver, the adhesive and the dispersant are added into water, mixed and dispersed to form an antibacterial finishing liquid; the fabric is immersed in the antibacterial finishing liquid for double dipping and double rolling, and dried and solidified to obtain the product.

Citation Information

Patent Citations

  • Antibacterial silk quilt coated with nano silver by layering and preparation method thereof

    CN109267232A

  • Polyacrylic ester coating adhesive emulsion and preparation method thereof

    CN101864024A

  • Ultraviolet-curing antibacterial material for 3D printing and preparation method of material

    CN108329437A

  • Antibacterial fabric based on plant dye dyeing and preparation method thereof

    CN113789649A

  • Composite antibacterial mildew-proof material and application thereof, and composite powder coating and preparation method thereof

    CN114223672A